Differential contributions of intra‐cellular and inter‐cellular mechanisms to the spatial and temporal architecture of the suprachiasmatic nucleus circadian circuitry in wild‐type, cryptochrome‐null and vasoactive intestinal peptide receptor 2‐null mutant mice. (2nd June 2014) - Pauls, S.; Foley, N. C.; Foley, D. K.; LeSauter, J.; Hastings, M. H.; Maywood, E. S.; Silver, R.
Abstract To serve as a robust internal circadian clock, the cell‐autonomous molecular and electrophysiological activities of the individual neurons of the mammalian suprachiasmatic nucleus (SCN) are coordinated in time and neuroanatomical space. Although the contributions of the chemical and electrical interconnections between neurons are essential to this circuit‐level orchestration, the features upon which they operate to confer robustness to the ensemble signal are not known. To address this, we applied several methods to deconstruct the interactions between the spatial and temporal organisation of circadian oscillations in organotypic slices from mice with circadian abnormalities. We studied the SCN of mice lacking Cryptochrome genes (Cry1 and Cry2), which are essential for cell‐autonomous oscillation, and the SCN of mice lacking the vasoactive intestinal peptide receptor 2 (VPAC2‐null), which is necessary for circuit‐level integration, in order to map biological mechanisms to the revealed oscillatory features. The SCN of wild‐type mice showed a strong link between the temporal rhythm of the bioluminescence profiles of PER2::LUC and regularly repeated spatially organised oscillation. The Cry‐null SCN had stable spatial organisation but lacked temporal organisation, whereas in VPAC2‐null SCN some specimens exhibited temporal organisation in the absence of spatial organisation. The results indicated that spatial and temporal organisation were separable, that they may have different mechanistic origins (cell‐autonomous vs. interneuronal signaling) and that both were necessary to maintain robust and organised circadian rhythms throughout the SCN. This study therefore provided evidence that the coherent emergent properties of the neuronal circuitry, revealed in the spatially organised clusters, were essential to the pacemaking function of the SCN.